Nutrition and Physical Activity Behavior in 11-14-Year-Old Schoolchildren in Serbia - Biljana Cvetković; Milan Cvetković; Tanja Petrušič; Višnja Đorđić; Saša Bubanj; Boris Popović; Slobodan Andrašić; Svetlana Buišić; Špela Bogataj (MDPI AG, 2021)
Regular physical activity and healthy diet have a significant positive impact on children's health. Lack of physical activity increases the risk of various diseases, while obesity has become an alarming health problem worldwide. The aim of this study is to investigate the patterns of physical activity and diet among 11-14-year-old school children in Serbia. The sample included 623 primary school children, of whom 333 were boys (53.45%) and 290 were girls (46.55%). The children were also divided according to their age/grade: fifth grade/11 years (24.40% (n = 152; M = 84, F = 68)), sixth grade/12 years (25.68% (n = 160; M = 91, F = 69)), seventh grade/13 years (26.81% (n = 167; M = 83, F = 84)) and eighth grade/14 years (23.11% (n = 144; M = 75, F = 69)). Children's lifestyle was assessed using two subscales of questionnaires based on the Health-Promoting Lifestyle Profile model II. The Mann-Whitney U test showed no statistically significant difference between boys and girls in the variables Nutrition (p = 0.81) and Physical Activity (p = 0.91). The Kruskal-Wallis test was applied and showed no statistically significant differences between children of different ages, regardless of gender, in the variable Nutrition (p = 0.63). However, differences were evident in the variable Physical Activity (p < 0.001), with the highest mean scores recorded in 12- and 13-year-old children and the lowest in 14-year-old children. Additionally, no statistically significant differences were found among boys as a function of age in the variables Nutrition (p = 0.55) and Physical Activity (p = 0.15), nor among girls in the variable Nutrition (p = 0.43), but in the variable Physical Activity (p = 0.01). In general, it can be concluded that the older primary school children have relatively satisfactory dietary and physical activity habits, but that these behaviors decrease with age, especially the level of physical activity. There is a need for better and more effective education of children about the benefits and importance of proper nutrition and regular physical activity.